The opemtive treatment of the caecum dilation and right abamasal deplacement case in a weaning calf - Veysi ASLAN; Kürşat TURGUT; Yılmaz KOÇ (Eurasian Journal of Veterinary Sciences)
A caecum dilatation and right abamasal deplacement case was determined at a male weaning calf of cross bread southern Anatolia Red (GAK) that was brought to the clinics of internal medicine of Veterinary Faculty at the same day, the caecum was discharged and the abamasum brought back in its right place by the fippropriate operative procedures. The calf was treated by applying antibiotics and liquid electrolites via intra peritonal and parenteral means. It was observed that the animal has been recovered in the 10th day of treatment.